Pena-Shokeir Syndrome - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1991)
An infant with Pena-Shokeir syndrome born to a cocaine using mother is reported from the University of Pennsylvania School of Medicine, Philadelphia, PA.